Enzymatic transfer of sialic acids modified at C-5 employing four different sialyltransferases - Groß, Hans Jürgen; Brossmer, Reinhard (Glycoconjugate journal, 1995)
We present kinetic studies on the enzymatic transfer of several synthetic sialic acid analogues, modified at C-5, to distinct glycoprotein glycans by sialytransferases differing in acceptor- and linkage-specificity. Biochemical properties of sialic acids were modified by introducing formyl-, trifluoroacetyl-, benzyloxycarbonyl-, and aminoacetyl-groups to the amino group at C-5 of neuraminic acid. The latter substitution renders the corresponding α-glyocoside resistant towards sialidases. The respective CMP-sialic acid analogues were prepared by CMP-sialic acid synthase with a yield of 13-55%.